2020
DOI: 10.1093/jnen/nlaa035
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CaMKII and GluR1 by the PSD-95-GluN2B Coupling-Dependent Phosphorylation of GluN2B in the Spinal Cord in a Rat Model of Type-2 Diabetic Neuropathic Pain

Abstract: The mechanisms underlying type-2 diabetic neuropathic pain (DNP) are unclear. This study investigates the coupling of postsynaptic density-95 (PSD-95) to N-methyl-D-aspartate receptor subunit 2B (GluN2B), and the subsequent phosphorylation of GluN2B (Tyr1472-GluN2B) in the spinal cord in a rat model of type-2 DNP. Expression levels of PSD-95, Tyr1472-GluN2B, Ca2+/calmodulin-dependent protein kinase II (CaMKII) and its phosphorylated counterpart (Thr286-CaMKII), and α-amino-3-hydroxy-5-methyl-4-soxazole propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“… 42 GluR1 is mainly expressed in superficial layer of spinal dorsal horn and funtion as an initial part of the signal related to the transmission and regulation of pain. 43 In this study, our result showed that the phosphorylated form of both Rac1 (p‐Rac1) and GluR1 (p-GluR1) was significantly increased in the BCP group than in the sham group. Treatment with shP-Rex2 significantly inhibited the upregulation of p‐Rac1 and pGluR1 in the BCP group.…”
Section: Discussionmentioning
confidence: 50%
“… 42 GluR1 is mainly expressed in superficial layer of spinal dorsal horn and funtion as an initial part of the signal related to the transmission and regulation of pain. 43 In this study, our result showed that the phosphorylated form of both Rac1 (p‐Rac1) and GluR1 (p-GluR1) was significantly increased in the BCP group than in the sham group. Treatment with shP-Rex2 significantly inhibited the upregulation of p‐Rac1 and pGluR1 in the BCP group.…”
Section: Discussionmentioning
confidence: 50%
“…In HFD/STZ models, insulin was reported to be decreased [ 40 ], increased [ 41 ], and unchanged [ 42 , 43 ] at 16 weeks with no clear relationship to DPN phenotype ( Table 2 ). In HFHS/STZ models, four studies [ 44 - 47 ] demonstrated an increase in insulin that corresponded with mechanical or thermal hyperalgesia. However, all these studies were of short duration (<5 weeks) where hyperalgesia is common ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both AMPAR levels at synapses and AMPAR-dependent synaptic transmission are reduced in hippocampal slices of newborn NL1 knockout mice (Zhu et al, 2020). A unique intracellular tyrosine in NL1 regulates AMPAR recruitment during synapse differentiation and potentiation (Letellier et al, 2018).…”
Section: Discussionmentioning
confidence: 99%